Glosa do postanowienia Sądu Najwyższego z dnia 27 listopada 2014 r., sygn. IV CSK 115/14 - Różowicz, Konrad (Studia Prawa Publicznego, 2019)
Glosa do postanowienia Sądu Najwyższego z dnia 27 listopada 2014 r., sygn. IV CSK 115/14